Long-term restraint stress as a predictor of insulin resistance development in experimental rats - K. B. Romanova; O. V. Hancheva; Yu. M. Kolesnyk (Zaporozhye State Medical University, 2023)
The aim of the work was to define the pattern of changes and pathogenetic mechanisms of glycemic curve shape during a glucose tolerance test in rats at 6, 15, and 21 weeks of environmental space restriction. Materials and methods. A total of 55 male Wistar rats aged 6-10 months were used and divided into 4 groups (1 - intact control, 10 rats; 2, 3 and 4 of 15 rats each, which were in conditions of restricted environmental space for 6, 15 and 21 weeks, respectively). Fasting plasma levels of glucose (test strips Test Strip II on a Glucocard glucometer (ARKRAY Inc., Japan)), insulin and corticosterone (by an immunoenzymatic method using commercial kits for rats from Monobind, USA) were measured, glucose tolerance tests (GTT) were performed, the HOMA index and the insulin/corticosterone ratio were calculated. Results. The 6-week environmental space restriction, immobility and complex communication relations resulted in a hypoinsulinemic-hypoglycemic type of the glycemic curve with high tissue glucose sensitivity in animals which were in the conditions described (the HOMA index was significantly decreased to 0.21 versus 0.55 in the control), the characteristic delayed hyperglycemic peak at the 30th min of the test slowly returned to the euglycemic level by only the 90th min against the 30th min in the controls. The 15-week restriction caused a hypoinsulinemic curve with preserved tissue glucose sensitivity (the HOMA index 0.33 versus 0.55 in the controls). Alterations in postprandial glucose absorption were manifested by the highest glucose concentration at the 15th min of the test, a very slow decrease in the glucose level in the post-absorption period not being restored to baseline values by the 90th min. The 21-week restriction shaped a diabetic type of the glycemic curve, impaired tissue glucose sensitivity (a substantial and significant increase in the calculated HOMA index from 0.55 in the controls to 0.95) and resulted in the development of insulin resistance. Conclusions. The environmental space restriction, immobility and complex communication relations gradually induce a range of disorders in animals and change the glycemic response shape to glucose load, impair prandial insulin secretion, augment hyperglycemic effects of counterinsular hormones (corticosterone), and realize dysfunctional manifestations of prandial/postprandial glycemia. 6 weeks of restrictions and challenges shape the hypoinsulinemic-hypoglycemic type of the glycemic curve with high tissue glucose sensitivity, while 15 weeks result in the hypoinsulinemic curve with preserved tissue glucose sensitivity. 21 weeks show the diabetic type of the glycemic curve with impaired tissue glucose sensitivity and the development of insulin resistance.